The Influence of Promotional Strategies and Prices on Interest Decisions of Prospective Students at Mitra Karya Rengasdengklok Vocational School - Paramita, Lilis; Kristanto, Yudi; Taryanto, Taryanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine the influence of promotional strategies and prices on prospective students' interest decisions, meaning to find out whether prospective students will be interested in Mitra Karya Rengasdengklok Vocational School. This research method uses quantitative data collection methods with questionnaires, the sample in this research consists of 65 potential respondents. Students of Mitra Karya Rengasdengklok Vocational School. By using a probability sample, the data analysis used is correlation regression, so it is clear how big the influence of promotion and price strategies is in choosing the decision of interest of prospective new students to explain this case. The results of research examining the influence of promotional strategies and prices on the decision of prospective students' interest in registering at Mitra Karya Vocational School have a significant effect on the decision of interest of prospective students to register at Mitra Karya Rengasdengklok Vocational School. amounted to 69.5%, while the remaining 30.5% was again influenced by other variables not included in this study.